2006
DOI: 10.1021/es061599r
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Photocatalytic Degradation of Azodyes in Aqueous AgI/TiO2 Dispersion

Abstract: AgI/TiO2 was prepared by the deposition−precipitation method and was found to be a novel visible light driven photocatalyst. The catalyst showed high efficiency for the degradation of the nonbiodegradable azodyes reactive red K-2G, reactive brilliant red X-3B, reactive red K-2BP, and reactive yellow KD-3G under visible light irradiation (λ > 420 nm). The catalyst's activity was maintained effectively after successive cyclic experiments under visible irradiation without the destruction of AgI. On the basis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(117 citation statements)
references
References 20 publications
5
108
1
3
Order By: Relevance
“…21 Furthermore, in the visible light irradiated AgI/ TiO 2 system, the formation of H 2 O 2 also was detected as shown in the previous work. 15 The results indicated that • OH and H 2 O 2 reactive species were involved in the photocatalytic bactericidal reaction. S. aureus was also killed efficiently in aqueous AgI/ TiO 2 suspensions under visible light irradiation.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…21 Furthermore, in the visible light irradiated AgI/ TiO 2 system, the formation of H 2 O 2 also was detected as shown in the previous work. 15 The results indicated that • OH and H 2 O 2 reactive species were involved in the photocatalytic bactericidal reaction. S. aureus was also killed efficiently in aqueous AgI/ TiO 2 suspensions under visible light irradiation.…”
Section: Resultsmentioning
confidence: 94%
“…15 In the present study, the photocatalytic inactivation of the pathogenic bacteria Escherichia coli and Staphylococcus aureus in an aqueous AgI/TiO 2 suspension under visible light irradiation was systematically studied from the mechanistic and kinetic viewpoints. The details of photocatalytic degradation of the cell wall and the cell membrane were characterized by TEM and FT-IR measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Maybe it was the first time to confessedly recognize the silver halide as photocatalyst. In 2006, a visible-light-induced photocatalyst AgI/TiO 2 was prepared by Chun Hu et al and was found to show high efficiency for the degradation of azodyes, which based on their previous work visible-light-driven photocatalyst AgBr/TiO 2 [115]. The above-mentioned is primary regarding the origin of silver halides on the photocatalysis application.…”
Section: What Is Silver Halide and Its Development In Nanotechnologymentioning
confidence: 99%
“…The above-mentioned is primary regarding the origin of silver halides on the photocatalysis application. From then on, tremendous works with respect to the property and morphology modification on silver halides sprang up to advance their photocatalytic performance [114][115][116][117][118][119][120][121].…”
Section: What Is Silver Halide and Its Development In Nanotechnologymentioning
confidence: 99%
“…[11][12][13][14][15][16][17] In particular, the treatment of wastewater from textile dyeing processes containing reactive dye stuffs should be mentioned. 18,19 For those applications, it is possible to use TiO 2 as a powder. However, for many applications it is more suitable to have the TiO 2 as a kind of photoactive coating on a substrate, which can be easily introduced into the application process and removed after the process is finished.…”
Section: Introductionmentioning
confidence: 99%